PEMBELAJARAN PAI DENGAN PENDEKATAN HUMANISTIK DALAM KURIKULUM MERDEKA: Pendekatan Humanistik, Pembelajaran PAI Dengan Pendekatan Humanistik, Pembelajaran PAI Dalam Kurikulum Merdeka - Okvani Kartika, Resti; Nabih Billah, Ahmad; Muqowim, Muqowim (al-Iltizam: Jurnal Pendidikan Agama Islam, 2024)
This article discusses the application of PAI learning with a humanistic approach in the independent curriculum. The facts show that technological developments that occur have a negative influence on character education and cause a decline in human attitudes so that appropriate learning approaches are needed. The humanistic approach is the main basis for increasing human values ​​to overcome the problem of students' moral decline. Therefore, the researcher used the library research method (Library Research) with content analysis techniques (content analysis). The results of this research found that PAI learning, the humanistic approach and the independent curriculum are in harmony in achieving the goal of forming students' characters with freedom based on humanity. So that PAI teachers can collaborate between humanistic approaches, PAI learning and independent curriculum to achieve success in forming students' character. The results of this research, although still simple, can be used as a reference for teachers to choose an approach that is appropriate to the applicable learning and curriculum.